Aspectos formais da linguagem em crianças com e sem desvio fonológico - Freitas, Carolina Ramos de (2014)
Objective: This research aims to investigate a possible relationship between the productive and perceptual phonological features and other formal aspects of language in children with phonological disorders (PD). It also aims to determine whether there is influence of phonemic discrimination in other linguistic subsystems, based on the performance of children with phonological subsystem changes and comparing the performance of children with typical language development (TLD), aged 5: 0 to 7:11. Method: The sample comprised 36 children of both sexes, and 19 had typical and 17 deviant phonological development. After conducting a speech and hearing screening, the children were subjected to Figures Test for Discrimination Phonemic - FTDP that assesses phonemic discrimination through minimal pairs. They were also subjected to Average Values Phrase Test, and there was a collection of the first five listed phrases in three ways: to tell a story based on four figures, answer five questions about their daily lives and describe a figure. Then the sentences were scored according to its complexity. In addition, children underwent the Expressive Vocabulary Test in an original way (TVExp-100th), with 100 images reordered by increasing degree of difficulty. For the analysis of the influence of correction the Spearman test was used and to compare the significance between the performances of the two groups the Mann-Whitney test was used, both with significance level set at p <0.05. Results: In children with PD, there were statistically significant differences in correlations between phoneme discrimination and other subsystems, and also in relation to the severity of the deviation and the number of acquired phonemes. In comparing children with TLD and children with PD, there was a statistically significant difference regarding the influence of phonemic discrimination only on population deviation. In addition, there is a statistically significant difference between the performance of children with and without phonological disorder, relative to phonemic discrimination, vocabulary and all evaluated levels of the questions and descriptions modality. Conclusion: Children with TLD do not suffer influences of auditory discrimination when compared with children with PD. And the phonemic discrimination plays an important role in developing phonological and other linguistic subsystems.